2014
DOI: 10.1155/2014/207465
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Emission, Energy, and Exergy Analysis of a C.I. Engine Using Mahua Biodiesel Blends with Diesel

Abstract: This paper presents an experimental investigation on a four-stroke single cylinder diesel engine fuelled with the blends of Mahua oil methyl ester (MOME) and diesel. The performance emission, energy, and exergy analysis has been carried out in B20 (mixture of 80% diesel by volume with 20% MOME). From energy analysis, it was observed that the fuel energy input as well as energy carried away by exhaust gases was 6.25% and 11.86% more in case of diesel than that of B20. The unaccounted losses were 10.21% more in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
(14 reference statements)
0
11
0
1
Order By: Relevance
“…Each tree yields about 20–40 kg of seed per year (Borugadda and Goud, 2012). Madhuca indica seed contains 35% oil and 16% protein (Panigrahi et al., 2014). Fresh Madhuca indica oil from properly stored seeds is yellow, while commercial oils are generally greenish yellow with an offensive odor and disagreeable taste (Puhan et al., 2005).…”
Section: Non-edible Vegetable Oils As Raw Materialsmentioning
confidence: 99%
“…Each tree yields about 20–40 kg of seed per year (Borugadda and Goud, 2012). Madhuca indica seed contains 35% oil and 16% protein (Panigrahi et al., 2014). Fresh Madhuca indica oil from properly stored seeds is yellow, while commercial oils are generally greenish yellow with an offensive odor and disagreeable taste (Puhan et al., 2005).…”
Section: Non-edible Vegetable Oils As Raw Materialsmentioning
confidence: 99%
“…where y i is molar ratio of the ith component in the exhaust gas, y e i is molar ratio of the ith component in the reference environment, R is the universal gas constant (8.314 kJ/kmol-K). If a given component does not exist in the environment, then the chemical exergy of the hydrocarbon in Gibbs free energy ( g) form is expressed as equation (19) as per Kopac and Kokturk. 33…”
Section: Thmentioning
confidence: 99%
“…17 The results show that by using the cottonseed and palm oils pure or blended with diesel for different engine loads the combination of exergy and gas emissions analyses is a very effective tool for evaluating the optimal loads that can be supplied by CI engines. 18 Panigrahi et al 19 concluded that by using mahua oil methyl ester and diesel up to 20%, the performance, emission energy and exergy part is very close with that of diesel. The results of a seven Brake Horse Power water cooled diesel engine fuelled with petro-diesel, and palm biodiesel showed a similar type energetic performance with petro-diesel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one research it was found that neem, karanja, rubber, jatropha, mahua are major candidates as they can be grown in diverse socio-economic and environmental conditions and also they are multipurpose plants which founds its applications in medicines, dyes, ornamental, feeds, soil enrichments, afforestation etc [4]. Nabnith panighari et al [5] have analysed the single cylinder diesel engine running with mahua biodiesel blends and they found that B20 fuel has higher thermal efficiency and brake specific fuel consumption (BSFC) compared to other blends and NOx emission is higher for biodiesel compared to diesel. S Sivalakshmi et al [6] have checked the performance of 4 stroke single cylinder diesel engine fuelled with Neem oil biodiesel and they found that lower blend ratio gives better performance compared to diesel fuel and combustion process is improved with biodiesel.…”
Section: Introductionmentioning
confidence: 99%